2000
DOI: 10.1902/annals.2000.5.1.166
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Preoperative Antibiotics on Success of Endosseous Implants at 36 Months

Abstract: The benefits of prophylactic antibiotics are well recognized in dentistry. However, their routine use in the placement of endosseous dental implants remains controversial. As part of the comprehensive Dental Implant Clinical Research Group (DICRG) clinical implant study, the preoperative or postoperative use of antibiotics, the type used, and the duration of coverage were left to the discretion of the surgeon. These data for 2,973 implants were recorded and correlated with failure of osseointegration during he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(106 citation statements)
references
References 7 publications
3
97
0
6
Order By: Relevance
“…Published literature in this context related to either use of AMAs by dental practitioners in routine clinical practice or the success and failure of oral implants with or without AMAs [23][24][25][26][27][28][29][30]. Only one study from Jordan had specifically reported the use of AMAs by dentists performing oral implant surgery [31].…”
Section: Introductionmentioning
confidence: 99%
“…Published literature in this context related to either use of AMAs by dental practitioners in routine clinical practice or the success and failure of oral implants with or without AMAs [23][24][25][26][27][28][29][30]. Only one study from Jordan had specifically reported the use of AMAs by dentists performing oral implant surgery [31].…”
Section: Introductionmentioning
confidence: 99%
“…19,20 The research to date with regard to efficacy of antimicrobial prophylaxis in reducing failure of integration of implants and reducing postoperative complications remains equivocal. 8,21,22 The General Dental Council (GDC) has stated that 'a UK-qualified dentist would not be expected to be competent to practise implant dentistry without undertaking • Suggests that there is currently a wide variation in prescribing patterns for antibiotic prophylaxis when placing dental implants.…”
Section: Introductionmentioning
confidence: 99%
“…It can be separated into the inflammatory phase, the proliferative phase, and the maturation phase. [4] Phase One: Inflammatory Phase…”
Section: Mechanism Of Wound Healing Following Implant Placementmentioning
confidence: 99%
“…Even with the most careful surgical manipulation of osseous tissues, the generation of a thin layer of necrotic bone in the periimplant region is inevitable. [4] In addition, exact microscopic fit between the implant and the surgical defect is not possible, leaving local areas of dead space where the implant does not directly contact osseous tissue.…”
Section: Mechanism Of Wound Healing Following Implant Placementmentioning
confidence: 99%